Geochemistry and Tectonic Setting of Pleistocene Basaltic Lava Flows in the Shahre-Babak Area, NW of Kerman, Iran: Implication for the Evolution of Urumieh- Dokhtar Magmatic Assemblage - S.Z. Hosseini (Journal of Sciences, Islamic Republic of Iran)
Pleistocene basaltic lava flows, consisting of trachybasalt and basaltic trachyandesite, cover an area north-northwest of Shahre-Babak in southeastern Iran. The whole rock chemistry indicates that the lavas are dominantly alkaline and mildly calc-alkaline. Variation diagrams of SiO2 with major and trace elements are consistent with fractional crystallization processes involving olivine, pyroxene, plagioclase, ± hornblende and Fe-Ti oxides. In both rock types trace element variations show similar high LILE/HFSE ratios, which along with their similar fractionation trend, implying a common magma source but different degrees of evolution. Their MORB normalized incompatible trace element concentrations show enrichment in LILE (e.g., Sr, K, Rb, Ba) and LREE (e.g., Ce), but depletion in HFSE (e.g., Ta, Nb, Ti, Zr, Hf, Y) and HREE (e.g. Yb). The Shahre-Babak alkaline basalts show characteristics of subduction related (active) continental margins, OIB and within-plate tectonic environments. Regarding the Late Miocene collision time between Arabia and Central Iran, the Shahre-Babak alkaline basaltic lavas should be collision related (post-collisional). Their enrichment in LILE and LREE relative to Ta and Nb can be explained either by: (a) presence of a subduction component or addition of an LILE-enriched, Nb-Ta poor fluid component to the mantle wedge or (b) crustal contamination of mantle-derived magmas during their ascent to the surface through assimilation and fractional crystallization (AFC) and or MASH (melting, assimilation, storage and homogenization). The magma erupted in a post-collisional tectonic setting and formed in a within-plate environment between two north-south running faults and is closely related to deep lithospheric fractures.